(untitled) (Journal of Nobel Medical College, 2012)
A prospective study of 20 comminuted femoral fractures, open and close, treated with interlocked intramedullary nailing. The mechanical strength of the nail and less invasive procedure has made the procedure preferable. Short Operative time and less blood loss was seen during surgical procedure. Out of 20 cases , 10 cases were taken from Nepal Medical College, Kathmandu and 10 cases from Nobel Medical College, Biratnagar, during years 2009 to 2011, which had been completed at least six months follow up. Almost all cases were relatively free from long term complication. The results were promising .All fractures healed within 6 months. DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7300 Journal of Nobel Medical College (2012), Vol.1 No.2 p.50-56